A COMPARATIVE ANALYSIS OF ECO-FRIENDLY CONSUMER TRENDS IN GREEN MARKETING IN THE DIGITAL AGE - Dr.P.Abarna, (EPRA International Journal of Research and Development (IJRD), 2024)
This research investigates consumer attitudes and preferences towards green marketing strategies, examining a diverse demographic spectrum encompassing age, gender, income, education, and nature of residence. Surveying a sample of 100 respondents in Tamil Nadu, the findings highlight the prominence of social media advertising as a key channel for eco-friendly initiatives. Noteworthy preferences include high endorsement of green certification and collaboration with non-governmental organizations, emphasizing the importance of transparent sustainability practices. The study suggests the need for nuanced marketing strategies tailored to diverse demographics and underscores the dynamic nature of consumer preferences in the sustainability landscape. Businesses are encouraged to balance established practices with emerging trends, fostering trust through transparent eco-friendly initiatives. This research provides valuable insights for businesses navigating the complexities of green marketing, aiming to resonate effectively with a diverse and conscientious consumer base.